PERAN RELIGIUSITAS DALAM PENGELOLAAN KANTOR AKUNTAN PUBLIK PADA MASA PANDEMI COVID-19 - Erfan Muhammad; Atik Abidah (Jurnal Ekonomi Syariah Pelita Bangsa, 2022)
The emergence of covid-19 as a non-natural disaster has an impact on the management of the Public Accounting Firm. There are problems in managing a Public Accounting Firm during the pandemic, including; limitations in carrying out audit procedures, the labor load remains high, and revenue declines because many companies are making losses. Religiosity can play a role in this problem, where with religiosity you can see things not only from the material side, but also look at life more broadly. This research was conducted using unstructured interviews with the head of a public accounting firm who are considered to have high religiosity. The results of the study indicate that religiosity has a role in the management of Public Accounting Firms during the pandemic, both in managing employees and in audit quality.